2013
DOI: 10.1021/am4000134
|View full text |Cite
|
Sign up to set email alerts
|

Superhydrophobic Surfaces on Light Alloy Substrates Fabricated by a Versatile Process and Their Corrosion Protection

Abstract: After hydrothermally treated in H2O (for Mg alloy and Al alloy) or H2O2 (for Ti alloy), microstructured oxide or hydroxide layers were formed on light alloy substrates, which further served as the active layers to boost the self-assembling of 1H,1H,2H,2H-perfluorooctyltriethoxysilane (PFOTES) and finally endowed the substrates with unique wettability, that is, superhydrophobicity. For convenience, the so-fabricated superhyrdophobic surfaces (SHS) were abridged as HT-SHS. For comparison, SHS coded as CE-SHS wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
102
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 211 publications
(102 citation statements)
references
References 32 publications
0
102
0
Order By: Relevance
“…53,54 Hydrothermal method Similar to the two methods above, the hydrothermal method is another important top-down approach for fabrication of superhydrophobic anticorrosive surfaces. [55][56][57][58][59][60][61] Here, the surface microstructures are synthesized from an aqueous environment under elevated heat and/or pressure. Hydrothermal methods are considered more environmentally friendly since the chemical used to create surface microstructures is only H 2 O or dilute H 2 O 2 .…”
Section: Etchingmentioning
confidence: 99%
See 2 more Smart Citations
“…53,54 Hydrothermal method Similar to the two methods above, the hydrothermal method is another important top-down approach for fabrication of superhydrophobic anticorrosive surfaces. [55][56][57][58][59][60][61] Here, the surface microstructures are synthesized from an aqueous environment under elevated heat and/or pressure. Hydrothermal methods are considered more environmentally friendly since the chemical used to create surface microstructures is only H 2 O or dilute H 2 O 2 .…”
Section: Etchingmentioning
confidence: 99%
“…Hydrothermal methods are considered more environmentally friendly since the chemical used to create surface microstructures is only H 2 O or dilute H 2 O 2 . 58 Li et al, reported a hydrothermal method to produce superhydrophobic zinc surface using a two-step approach: (1) autoclaving zinc in pure water at 120°C for surface roughening; (2) immersing in ethanol solution containing 1H,1H,2H,2H-perfluorooctyltriethoxysilane (PFOTES) for surface hydrophobization. 57 From the viewpoint of corrosion protection, hydrothermal methods are also more favored than chemical etching because of the formation of oxide or hydroxide protective layers.…”
Section: Etchingmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to facilitate the corrosion protection of various metallic substrates, versatile alternative practical coatings are being continuously developed such as conducting/ electroactive polymers, [10,11] conventional polymers containing filler with large aspect ratio [12,13] and polymer coatings with superhydrophobic surface [14,15]. Recently, great attention is paid to the potential of applications on bio-mimetic materials with super-hydrophobic surfaces structure due to their diverse potential and unprecedented hierarchical surfaces [16][17][18][19][20][21][22][23][24][25][26].…”
mentioning
confidence: 99%
“…Water drops on such surfaces cannot penetrate the micro-or nanostructures and wet the surface, resulting in extremely high contact angles; thus, these naturally occurring leaves exhibit considerable superhydrophobicity. Numerous methods, including photolithography [6], plasma treatment [7], templates [8], chemical deposition [9], solgel processes [10], chemical vapor deposition (CVD) [11], casting, and chemical etching [12], have been utilized to fabricate superhydrophobic surfaces. Several studies have been reported on using polymers and polymer nanocomposites for various applications such as fabricating hydrophobic/superhydrophobic surfaces [13][14][15][16][17][18][19][20][21].…”
mentioning
confidence: 99%